HUMAN NATURE BASED ON AL-QUR’AN AS THE BASIC OF EDUCATION DEVELOPMENT - Abdul Kodir; Wawan Sonjaya (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This research focuses on perspective of human nature based on Al-Qur‟an as the basic of education development. It used descriptive qualitative method of research as well as library research which aims at collecting data and information from various literatures available in the library such as books, magazines, scripts, notes, histories, and other documents. The results of this research are drawn into conclusion, among others: first, based on all terms refering to human meaning, it can be defined that human nature required in Al-Qur‟an apparently leads to the term al-insân. On the other side, from human structure‟s perspective, Al-Qur‟an describes human as a creature consisting of physical and spiritual elements. Meanwhile from his position and role, human nature based on Al-Qur‟an is described as Allah‟s servant and Allah‟s khalifah on Earth. Second, there is a close relationship both directly and indirectly with education concept in Al-Qur‟an. Third, the concept of human nature in Al-Qur‟an which cannot be separated from its education concept, thus, has a basic implication toward all education aspects, especially, in vision, orientation and objective of education, curriculum, methodology of education and evaluation on education. Fourth, process of education development based on concept of human nature in Al-Qur‟an including objective, curriculum, methodology, and evalution of education aspects, basically, is understood as efforts or ikhtiar to develop all human existences in the term of totality, structure, position, role and other their own potential values.